Understanding Diversity in Organizations Paradigmatically and Methodologically - Vedran Omanovic (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper is part of a larger dissertation project named: A Production of Diversity: Appearances, Ideas, Interests, Actions, Contradictions and Praxis. In this dissertation project, which is planned to be completed by the first half of 2006, I have attempted to describe, understand and analyse a process of diversity production at a large manufacturing company, which is located in Sweden and owned by a large American company (for the reason of confidentiality the name of the studied company, which is a large, technical-oriented company, has been changed and some of the information is modified, while another cannot be offered because it would expose the company. The studied manufacturing company will from now be called Diversico). My ambition with this paper is to call attention to different paradigmatical and methodological ways of understanding and studying diversity in organizations. A starting-point for my discussion here is an assumption that researchers, by exploring different social phenomena (including diversity in organizations), bring their different sets of assumptions to what the studied phenomenon is (or could be) but also at the same time make assumptions on what organizations are (or could be). In other words, researchers, by studying diversity in organizations (as well as other social phenomena) construct ideas of diversity by positioning this phenomenon differently, asking different questions or designing research projects differently. In that sense I try to actively engage in both showing some benefits and limits in the present literature and searching for new theoretical and methodological possibilities. In that sense, I give some empirical illustrations inspired by one of these other possibilities. More concretely, I show how my study fulfils images of diversity as actively produced and positioned significant issues, and as domination of particular sectional interests. Furthermore I give illustrations of universalization and naturalization of some aspects of diversity, as identified in the studied process of diversity production at the manufacturing company.
Keywords: 330; Diversity; Critical Theory; Social-Historical Context and Domination; Diversity Management